Epidermal carcinoma: a five year (1981-1985) pathological analysis at Chiang Mai University Hospital - Theetranont C. (2014)
A total of 414 cases of epidermal carcinoma registered at the Department of Pathology, Faculty of Medicine, Chiang Mai University during the years 1981 to 1985 were analysed in detail. The disease was more prevalent in males than in females. The incidence was 55.56 per cent in males and 44.44 per cent in females. At the age interval between 50 to 79, epidermal cancers were most frequently seen. Most of the patients were farmers. The patients usually came to the hospital with signs and symptoms of mass and ulcer. The histological cell types were squamous cell carcinoma (50.25%), basal cell carcinoma (34.54%), malignant melanoma (14.01%) and other (1.21%). The etiology of epidermal carcinoma is not definitely known, therefore, the possible epidemiologic etiology was briefly discussed.